1998
DOI: 10.1073/pnas.95.13.7480
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of histone H3 at serine 10 is correlated with chromosome condensation during mitosis and meiosis in Tetrahymena

Abstract: H3 phosphorylation has been correlated with mitosis temporally in mammalian cells and spatially in ciliated protozoa. In logarithmically growing Tetrahymena thermophila cells, for example, H3 phosphorylation can be detected in germline micronuclei that divide mitotically but not in somatic macronuclei that divide amitotically. Here, we demonstrate that micronuclear H3 phosphorylation occurs at a single site (Ser-10) in the amino-terminal domain of histone H3, the same site phosphorylated during mitosis in mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
303
0
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(324 citation statements)
references
References 38 publications
15
303
0
6
Order By: Relevance
“…H3 phosphorylation at Ser10 is governed by the activity of aurora/Ipl1 kinases (Speliotes et al, 2000;Giet and Glover 2001;Crosio et al, 2002) in competition with the phosphatase activity of the serine/threonine protein phosphatase 1 (Hsu et al, 2000;Murnion et al, 2001). It has been shown that Ser 10-modified histone colo-calizes with the human condensin complex during G2/ prophase (Schmiesing et al, 2000), suggesting that this modification may have a role in destabilizing local chromatin structure to allow access of condensation factors to DNA or in recruiting the condensation machinery on the modified histone amino-terminal tail (Wei et al, 1998;Schmiesing et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H3 phosphorylation at Ser10 is governed by the activity of aurora/Ipl1 kinases (Speliotes et al, 2000;Giet and Glover 2001;Crosio et al, 2002) in competition with the phosphatase activity of the serine/threonine protein phosphatase 1 (Hsu et al, 2000;Murnion et al, 2001). It has been shown that Ser 10-modified histone colo-calizes with the human condensin complex during G2/ prophase (Schmiesing et al, 2000), suggesting that this modification may have a role in destabilizing local chromatin structure to allow access of condensation factors to DNA or in recruiting the condensation machinery on the modified histone amino-terminal tail (Wei et al, 1998;Schmiesing et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of this modified histone has been correlated with mitotic chromosome condensation in several eukaryotic systems (Hendzel et al, 1997;Wei et al, 1998). H3 phosphorylation at Ser10 is governed by the activity of aurora/Ipl1 kinases (Speliotes et al, 2000;Giet and Glover 2001;Crosio et al, 2002) in competition with the phosphatase activity of the serine/threonine protein phosphatase 1 (Hsu et al, 2000;Murnion et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of histone H3 at serine 10 is commonly used as a marker of mitotic progression [22,23]. HeLa cells were treated with or without CEP-11004 at 5 h after release from G1/S-phase thymidine block and allowed to incubate for an additional 4 h. Cells were then fixed and processed for immunofluorescence of cyclin B1 and phospho-histone H3 (pH3) to identify the mitotic cells.…”
Section: Cep-11004 Delays Histone H3 Phosphorylation In Early Mitosismentioning
confidence: 99%
“…Despite its longstanding history (Stevely and Stocken, 1966;Gutierrez and Hnilica, 1967) and the presence of numerous serine, threonine, and tyrosine residues speckled throughout the primary sequences of histone proteins. Early work in this area focused primarily on the phosphorylation of linker histones (eg, H1, Sweet and Allis, 1993) and of the core histone H3 (eg, H3S10 phosphorylation (H3S10p)) as universal markers of mitotic and meiotic chromatin condensation (Wei et al, 1998(Wei et al, , 1999. More recently, studies have begun to examine the role of phosphorylation on other core histone proteins, such as H2B, which was only recently demonstrated to function during apoptotic chromatin compaction (Ajiro, 2000;Cheung et al, 2003).…”
Section: Histone Phosphorylation and Cross Talk Interactions In The Cnsmentioning
confidence: 99%